BASIC PATHOGENETIC MECHANISMS OF ACUTE INTESTINAL PERFORATION IN PATIENTS WITH POSTOPERATIVE PERITONITIS - V. G. Lubyanskiy; A. N. Zharikov (Acta Biomedica Scientifica, 2012)
Causes of acute perforations of the small intestine were studied in the survey of 60 patients with postoperative peritonitis. A morphological study of the wall of the small intestine at different terms of peritonitis, mesenteri-cography intraoperative duplex scanning of small and large mesenteric arteries, as well as the interpretation of the major changes in the hemostatic system and humoral parameters in the systemic circulation and the intestinal contents. Found that in the pathogenesis of acute small bowel perforation peritonitis against the leading role of microcirculatory disorders caused by reperfusion syndrome, which occurs in the appearance of the development process and sometimes in the treatment of enteral insufficiency.